Współpraca państw Azji w zakresie polityki monetarnej - Żukrowska, Katarzyna (The co-operation of Asian states in the area of monetary policy, 2009)
Asian states are advanced in liberalizing their trade in goods and services, as well as capital flows. This stage of development requires moving towards more advanced co-operation in monetary policies, what is done in different institutional structures and configurations of participants. The main hub is created in this area by ASEAN, ASEAN+3 and ASEAN+6. Nevertheless, the process does not end on the mentioned groupings and has a strong impact on policies applied also in so-called nearest neighbourhood. Recently, the structures established in the process of liberalizing trade resemble classical spaghetti bowl, what is quickly followed by another bowl embracing states who co-operate in monetary matters. The co-operation in financial and monetary matters can be divided into clear four stages, from which the first is marked by departure from golden standard and energy crisis in 1973, while the last is marked by the 2008/2009 financial crises
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67, s. 89-102